Non-destructive estimation of 3D residual stress for peened materials using X-ray diffraction and eigenstrain theory - Takeshi KITAZAWA; Ryohei OKUI; Yuto SANO; Masaru OGAWA (Mechanical Engineering Journal)
Residual stresses generated by machining operations affect the dimensional accuracy and fatigue strength. However, fatigue strength can be improved by applying compressive residual stress through surface modification such as peening and carburising. If the three-dimensional residual stress of various surface finished materials can be identified, it will be possible to evaluate the quality and consider the optimal surface-finishing method. Currently, methods for identifying residual stress include repeated surface measurement using X-ray diffraction and electropolishing. However, since electropolishing releases residual stress, the original residual stress cannot be accurately measured. In addition, neutron diffraction is only available at specialized facilities and cannot be used on-site. Therefore, a three-dimensional residual stress estimation method using eigenstrain theory and X-ray diffraction has been proposed. This method uses an inverse analysis to estimate the eigenstrain, which is the source of residual stress, from the surface elastic strain measured non-destructively by the X-ray diffraction method. The three-dimensional residual stress distribution can be obtained by inputting the estimated eigenstrain into a finite element model. The purpose of this study is to propose an inverse analysis method that enables relatively accurate estimation of the three-dimensional residual stress in peened materials using X-ray diffraction and the eigenstrain theory. In order to demonstrate the effectiveness of this method, numerical simulations and demonstrations were carried out. The application of the method to a model assuming a laser shock-peened residual stress field showed that the three-dimensional residual stresses could be estimated with relatively high accuracy using this method, even when measurement errors were taken into account. The method was also applied to an actual laser shock-peened material, and the estimated residual stresses were compared with those measured by the X-ray diffraction method. As a result, although further improvement in the estimation accuracy is needed, the residual stresses estimated by this method show a rough distribution trend with respect to the measured residual stresses.